Thermal extraction of bamboo with various solvents - Kim, Junghee (2010)
This thesis is to describe the potential of improvement by liquefaction with various solvents in pyrolysis in terms of conversion of bamboo to gas and liquid and quality of the bio-oils and residues produced.